(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: The study was conducted with the aim of describing the current status of hospital-acquired infections and some related factors in patients with airway intervention in the intensive care units of Nghe An Obstetrics and Pediatrics Hospital in 2024. Subjects and methods: Cross-sectional descriptive study with analysis on 339 patients with airway intervention. Results: Mainly patients are young and decrease by age group, in which newborns account for the highest rate of 56.6%; 45.1% of patients have respiratory diseases. The most commonly prescribed invasive procedures were 3 (39.2%); patients with mechanical ventilation and nasogastric tubes accounted for the highest proportions, 98.2% and 94.1%, respectively. The proportion of patients with hospital-acquired respiratory tract infections was 16.2%; of which the highest site of infection was pulmonary infections (42.6%), followed by blood infections (41.0%), and finally surgical site infections (9.8%) and urinary tract infections (6.6%). The causative agent of hospital-acquired infections was gram (-) with the highest proportion of 72.1%; Klebsiella aerogenes was the cause of hospital-acquired infections with the highest proportion (34.5%). Factors that increase the risk of hospital-acquired infections in patients with airway intervention include: patients who have undergone surgery, patients with central catheters. Conclusions: The rate of hospital-acquired infections in patients with airway intervention is 16.2%. The rate of children who recover from the disease is high. The main causative agents are gram (-) bacteria.